Life events and their association with changes in the frequency of transport use in a large UK sample. (July 2022) - Whittle, Colin; Whitmarsh, Lorraine; Nash, Nicholas; Poortinga, Wouter
Highlights: Life events and changes in frequency of mode use over two years are associated. Transport specific events and changes in frequency of mode use over two years are associated. Relocators more likely to have also decreased their bus, train, and bicycles use. New parents less likely to have also increased their bus, train, and bicycle use. Changes in car use most strongly related to changes in context. Abstract: From a mobility biographies perspective, and in line with the habit discontinuities literature, consistency in travel behaviours is context dependent and as such, will be more amenable to change following changes in context that disrupt habitual travel behaviour. Using the UK Household Longitudinal Study (UKHLS), a large-scale, longitudinal, national survey, this study investigates associations between disruption (in the form of life events and transport specific events) and changes in the frequency of car, bus, train, and bicycle use over a two-year period. The analysis extends previous research in this area by considering changes in the frequency of travel for all purposes, not only for commuting. Further, the study tested the self-activation hypothesis through an interaction between experiencing a life event and environmental concern. The results show that residential relocation and parenthood were associated with significant changes in frequency of travel mode use. Relocation showed the most consistent pattern away from car, bus, train, and cycling, while parenthood showed a consistently lower likelihood of increasing use of these modes (except car), but no greater likelihood of decreasing. Transport specific events often accounted for greater likelihood of change in travel mode use – for example, obtaining a driving license, changing the number of cars in the household, and changing to/from urban settings had large associations with changes in travel behaviours – although these were not consistent across modes. Overall, this suggests that changes in the use of the different transport modes were differentially susceptible to the life event and transport specific events.